Severe primary pulmonary lymphangiectasis in a premature infant: Management and follow up to early childhood. Issue 1 (25th February 2015) - Reiterer, Friedrich; Grossauer, Karin; Pfleger, Andreas; Häusler, Martin; Resch, Bernhard; Eber, Ernst; Popper, Helmut; Urlesberger, Berndt
Abstract: Primary pulmonary lymphangiectasis (PPL) is a rare congenital developmental abnormality of the lung with a generally poor prognosis. Only a limited number of patients with neonatal‐onset PPL have been reported to survive. We present the case of a male preterm infant (gestational age 34 weeks 6 days) with histologically confirmed PPL, complicated by hydrops fetalis, bilateral hydrothorax (treated in utero with pleuro‐amniotic shunts), and immediate respiratory distress at birth. He survived after extensive neonatal intensive care therapy and was discharged home at the age of 7 months. At last follow up he was 3 years 7 months old, still requiring assisted ventilation via tracheostomy, having recurrent episodes of wheezing and had mild global developmental delay. This case demonstrates that survival beyond the neonatal period is possible even with severe PPL but long‐term morbidity may be relevant, and multidisciplinary management and close follow up are essential.